2010
DOI: 10.1586/erc.10.143
|View full text |Cite
|
Sign up to set email alerts
|

Combination of telmisartan plus amlodipine in the treatment of hypertension: review of results

Abstract: The rate of control of hypertension remains suboptimal despite widespread educational programs and an increasing number of novel medications. The combination of drugs with different mechanisms of action has become an alternative to improve blood pressure reduction and control, enhance adherence to the treatment and reduce adverse events. Telmisartan and amlodipine in monotherapy provide effective blood pressure lowering at all clinically relevant doses, but less than 50% of stage 1 and 2 achieve the target blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Many authors have demonstrated the superiority of telmisartan when combined with other antihypertensives like amlodipine or HCT compared to monotherapy. [11][12][13][14]. Telmisartan combinations were also better in BP reduction compared to other ARB combinations [15].…”
Section: Open Accessmentioning
confidence: 85%
“…Many authors have demonstrated the superiority of telmisartan when combined with other antihypertensives like amlodipine or HCT compared to monotherapy. [11][12][13][14]. Telmisartan combinations were also better in BP reduction compared to other ARB combinations [15].…”
Section: Open Accessmentioning
confidence: 85%
“…There is also evidence that a combination of the ARB, telmisartan, and the CCB, amlodipine, provides superior BP lowering compared with that of the individual monotherapies (15,16). This combination has also been demonstrated to be effective in patients at all stages of hypertension, as well as in those with added risk such as comorbid obesity, diabetes or metabolic syndrome (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%